2018
DOI: 10.1590/1413-70542018425020418
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of photosynthesis in black pepper plants under different shade levels promoted by intercropping with rubber trees

Abstract: Plants of black pepper (Piper nigrum L.) may display changes in their photosynthetic activity as a result of environmental seasonal changes. Intercropping with tree species may represent an alternative to mitigate the impacts of climatic changes on crops. The objective of this work was to evaluate the physiological responses of photosynthesis in black pepper plants under different shade levels promoted by intercropping with rubber trees (Hevea brasiliensis (Willd. ex A. Juss.) Müll. Arg. The photosynthetic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
2
4
0
1
Order By: Relevance
“…Protected environments influenced the most variables; there was a difference among the containers only for plant height at 30 DAT, stem diameter at 15 and 30 DAT, and number of flowers at 90 DAT ( Table 2). The shading levels of the protected environment affected pepper cultivation more than the color of pots, as greater shading favored growth, development, and production of the plants, in agreement with Zhu et al (2012) and Oliveira et al (2018), who had verified that this species adapted better in shaded environments. TABLE 2.…”
Section: Resultssupporting
confidence: 75%
“…Protected environments influenced the most variables; there was a difference among the containers only for plant height at 30 DAT, stem diameter at 15 and 30 DAT, and number of flowers at 90 DAT ( Table 2). The shading levels of the protected environment affected pepper cultivation more than the color of pots, as greater shading favored growth, development, and production of the plants, in agreement with Zhu et al (2012) and Oliveira et al (2018), who had verified that this species adapted better in shaded environments. TABLE 2.…”
Section: Resultssupporting
confidence: 75%
“…Besides, other factors, this behavior can be explained by photoassimilate production reductions (Tatagiba, Pezzopane, & Reis, 2015) due to stomatal closure under water deficit conditions (Peloso, Tatagiba, & Amaral, 2017), limiting vegetative crop growth. This could be observed in various crops such as black pepper (Piper nigrum), bell pepper (Capsicum annuum), lilac (Syringa oblata), and euonymus (Euonymus japonicus) (Oliveira, Oliosi, Partelli, & Ramalho, 2018;Sui, Mao, Wang, Zhang, & Zhang, 2012;Wu, Chow, Liu, Shi, & Jiang, 2014). Our results demonstrate that the water irrigation volume applied to meet crop water needs (100% by SIC) favored black pepper growth.…”
Section: Vegetative Growth Parameterssupporting
confidence: 51%
“…Thus, from the results of the present research, it is inferred that, at least in part, the cultivation with a live tutor of G. sepium associated with the supply of adequate amounts of N can benefit the black pepper in periods of the year of lower water regime. Oliveira et al (2018), when evaluating physiological responses to photosynthesis in black pepper plants in intercropping with rubber trees, observed that in summer, there was lower temperature and higher A value in treatments with rubber trees 2 and 5 meters away from the pepper tree, when compared to A values in plants in full sun, suggesting that during the warmer periods of the year shade can improve the photosynthetic functioning of black pepper, as previously reported for other species (Dai et al,, 2009;Zhu et al, 2012). It is well known that shading causes microclimatic changes in many agricultural crops, especially in plants located in rows closest to trees, resulting in physiological and growth changes (Partelli et al, 2014;Araújo et al, 2016;, which agrees with the findings of the present study since the SL, due to its crown, promotes certain shading of the black pepper tree.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were performed between 9 and 11 h, under ambient CO 2 concentration (c.a. 398 µmol CO 2 mol −1 ) and under saturating photosynthetically active radiation of 1,000 µmol m -2 s -1 (Oliveira et al, 2018;Silvestre et al, 2017). The instantaneous water use efficiency (WUE) was estimated as the quotient between A and E (Hatfield et al, 2011).…”
Section: Leaf Gas Exchangementioning
confidence: 99%